THE HEAVY LOAD OF THE BACKPACK ON THE SHOULDER POSITION AT THE AGE OF 12-15 YEARS AT SMPN 56 SURABAYA - Emilia Devi Dwi Rianti; Wahyuni Dyah Parmasari; Ayly Soekanto (LPPM Universitas PGRI Semarang, 2024)
Using backpacks causes many problems for the body and has a negative impact on the user. Continuous use of a backpack will cause irreversible changes to the user. The heavy load on a backpack doesn't just have an impact on shoulder pain. Analytical observational method with a cross-sectional approach, the research was carried out by weighing the bag, distributing questionnaires to assess the length of time the bag was used and age, and measuring the position of the right and left shoulders using a measuring scale. Results; bag weighing ± 3.52 kg with a minimum bag weight of 1.90 kg and a maximum of 7.6 kg. using the bag on average ±27.25 minutes, with a minimum time of 5 minutes and a maximum time of 120 minutes. The average left shoulder posture is ± 124.28, the minimum value is 108 and the maximum value is 145. The average right shoulder posture is ± 123.50, the minimum value is 107 and the maximum value is 141. Conclusion; there is no relationship between the weight of the bag used by the respondent and the posture of the respondent's right shoulder, as evidenced by the resulting significance value of 0.607 <0.05, there is no relationship between the weight of the bag used by the respondent and the posture of the respondent's left shoulder, as evidenced by the resulting significance value of 0.848 < 0.05, the weight of the bag used is still normal and has a value below 10% of the student's body weight.